Determinants of health-related quality of life in stable chronic obstructive pulmonary disease patients - Shaimaa S. Abdelrheem; Basma M. Osman; Gehad A. Mohamed; Hasnaa K. Mohammed; Taher M. Darwish; Aliae A.R. Mohamed Hussein; Hend M. Sayed; Ebtsam S. Abdul-Kareem (Egyptian Journal of Chest Disease and Tuberculosis)
Background Chronic obstructive pulmonary disease (COPD) is considered a public health problem. Health-related quality of life (HRQoL) in stable COPD patients is influenced by many factors. Aim The aim of the study was to assess the determinants influencing the HRQoL of stable COPD patients (GOLD I–III). Patients and methods A cross-sectional study of 150 stable COPD at Aswan University Hospital. Tools of data collection included spirometry, the COPD and Asthma Sleep Impact Scale-7, the Hospital Anxiety and Depression Scale, and the COPD-specific version of the St George’s Respiratory Questionnaire for COPD patients (SGRQ-C). Results Regression analysis showed that total SGRQ-C scores were significantly higher with patients’ age, comorbidity, dyspnea severity (modified Medical Research Council scale ≥2), frequent exacerbations (≥2 in the last year), sleep quality, and mental health. While forced expiratory volume in first second (% pred) showed a significant negative relationship between physical activity and SGRQ-C total score, smoking and BMI had no significant influence on the quality of life. Conclusion The majority of stable COPD had a low level of HRQoL. Age, presence of comorbidities, increased dyspnea, and more than two previous exacerbations in the last year were contributing factors. We recommend improving HRQoL with a multifaceted approach. Screening and early intervention for these factors such as sleep impairment, depression and anxiety, and pattern of physical activity with effective disease management might have a promising potential to enhance COPD patients’ quality of life.